An Analysis of Students’ Ability in Writing Recount Text at the Tenth Grade Students’ - Jenap Akdwi Fisya; Nora Fudhla (Universitas Negeri Padang, 2022)
The goal of this study is to understand the students' strengths and challenges with regard to linguistic elements and general structure when creating recount texts. The researcher takes a quantitative method in this study. The questionnaire and writing test were the two tools employed in this study. There were 150 students in all, 110 students participated in the questionnaire sample, and 24 students took the writing test. The sampling method used for this study's sample selection was proportional stratified random sampling with the Slovin formula.Questionnaires and writing test were used to find out the ability and difficulty that the students found in writing recount text, especially the generic structure and language features. The average percentage for the questionnaire were 64,13%. It means that the ability of the students’ was in the “Easy” level. Average scores of the student’s writing test were 65,45%. It means that the ability of the students’ were in the “Good“ level. For generic structures, it is quite difficult for students to make generic structures correctly when writing recounts, namely orientation, event, and reorientation. For language features, students have difficulty in distinguishing between nouns and pronouns. As the results, it turns out that the students' ability in writing recount texts is quite good with a “Good” scale and there are no significant difficulties faced by the student’s in SMA N 2 Gunung Talang ehen writing recount text in terms of generic structure and language features.